2011
DOI: 10.1097/mpa.0b013e3181f749d3
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features and Prognosis of Mucinous Cystic Neoplasm With Ovarian-Type Stroma

Abstract: Mucinous cystic neoplasm is a rare but distinctive pancreatic cystic neoplasm with a favorable overall prognosis. All MCNs should be resected to prevent malignant changes but can be observed for an appropriate time when the lesion is small without the presence of mural nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
115
3
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(141 citation statements)
references
References 7 publications
16
115
3
7
Order By: Relevance
“…The clinical characteristics of the patients are in accordance with the literature [1,2,3,4,5,6], showing a nearly exclusive occurrence in middle-aged females, paucity of symptoms and localization in the tail of the pancreas [1,2,7,8,9]. The spectrum of the histological grade is nearly similar to that of Crippa et al [2].…”
Section: Discussionsupporting
confidence: 74%
“…The clinical characteristics of the patients are in accordance with the literature [1,2,3,4,5,6], showing a nearly exclusive occurrence in middle-aged females, paucity of symptoms and localization in the tail of the pancreas [1,2,7,8,9]. The spectrum of the histological grade is nearly similar to that of Crippa et al [2].…”
Section: Discussionsupporting
confidence: 74%
“…Another added challenge is the pancreatic duct communication that theoretically is only patent in IPMNs. Despite this, a study showed that at least 15% of pathologically confirmed MCAs had a communication between the lesion and the MD (13).…”
Section: Mcasmentioning
confidence: 99%
“…There are four main types of PCNs: IPMNs, MCAs, serous cystadenomas and solid pseudopapillary neoplasms (Table I). As its name indicates, these lesions have a potential for malignant transformation (10) that broadly ranges from 1% to 36% (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, surgical resection is advocated as the primary treatment modality. However MCNs have a low prevalence of invasive carcinoma: indeed, in a recent large series, invasive carcinoma accounted for 3.9% to 16% of lesions in the pancreas (6,7) and 10% of those in the liver (8). Recently, the term MCN has been challenged by Albores-Saavedra et al (9,10), who favor dividing MCNs into two types: "pure MCNs" and "nonmucinous cystadenomas of the pancreas with pancreatobiliary phenotype and ovarian-like stroma".…”
mentioning
confidence: 99%